PDB Bantuan Alat Dan Pelatihan Peningkatan Kemampuan Masyarakat Dalam Pengolahan Limbah Kayu Menjadi Produk Homedecor - Nizaora, Ditha; Fahmiroah, Feti; Fatmawati, Anni; Shyafary, Darius; Soeprapto, Etwin Fibrianie (Jurnal Pengabdian kepada Masyarakat Nusantara, 2025)
Waste is the result of production processes that are no longer needed. Through the 5R's (Reuse, Recycle, Replant, Reduce, Replace) program, waste can be transformed into items that have value. Pine waste, or often called Dutch teak, is wood that has beautiful fiber characteristics and is commonly used to make furniture products. When this wood is processed into furniture, it produces a lot of leftover pieces that are no longer used and are simply thrown away. Based on this problem, Bakungan Kaltim and Samarinda State Polytechnic held a village development activity. The participants are a team of village volunteer firefighters who are members of the village youth group. The implementation of this activity focused on training and assistance in the design of processed wood waste products into home decor products. The method of implementation of the activities is training, assessment and mentoring. The results of the training, in the form of lights, in addition to the provision of tool assistance to the group, also increased youth empowerment as measured through the distribution of questionnaires.